2012
DOI: 10.1111/1462-2920.12021
|View full text |Cite
|
Sign up to set email alerts
|

Novel acid resistance genes from the metagenome of the Tinto River, an extremely acidic environment

Abstract: Microorganisms that thrive in acidic environments are endowed with specialized molecular mechanisms to survive under this extremely harsh condition. In this work, we performed functional screening of six metagenomic libraries from planktonic and rhizosphere microbial communities of the Tinto River, an extremely acidic environment, to identify genes involved in acid resistance. This approach has revealed 15 different genes conferring acid resistance to Escherichia coli, most of which encoding putative proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 71 publications
8
70
0
4
Order By: Relevance
“…The DnaK molecular chaperone (U-57) is a ubiquitously distributed class I stress protein, which tolerates the low pH potentially through regulating the biogenesis or stabilization of the F-ATPase compound [13,24]. The functions of Clp protease (U-38) and methyltransferase (U-41) have been corroborated by a previous study [17]. Only SMU_1725 (U-23), mreD and gbpB (U-8) were newly identified functional genes from S. mutans UA159.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…The DnaK molecular chaperone (U-57) is a ubiquitously distributed class I stress protein, which tolerates the low pH potentially through regulating the biogenesis or stabilization of the F-ATPase compound [13,24]. The functions of Clp protease (U-38) and methyltransferase (U-41) have been corroborated by a previous study [17]. Only SMU_1725 (U-23), mreD and gbpB (U-8) were newly identified functional genes from S. mutans UA159.…”
Section: Resultsmentioning
confidence: 70%
“…Both the inserts orf1 and ffh are known aciduric-related genes. The former encodes RNA-binding protein and a separate functional metagenomics study of the environmental sample confirmed its function [17], the latter comes from the S. mutans strain [11]. The purpose of construction of the strain E. coli DH10B/pSL-ffh and its functional verification was to detect whether the acid-resistant genes from oral bacteria could be heterologously expressed in E. coli .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional analyses of environmental genomic libraries are not designed to identify genes involved in uptake, transport, and nutrient metabolism processes (Mirete et al 2007;Guazzaroni et al 2013). While these functions could be studied using microarrays, the nature of the samples and the limited availability of universal controls impose further complications for understanding the intensity of the detected signals and their correlation with specific species.…”
Section: Scope and Limitations Of Genomic Approachesmentioning
confidence: 99%